Penerapan Fungsi Manajemen Dakwah dalam Meningkatkan Kinerja Pegawai Kantor Urusan Agama (KUA) Danau Kerinci - Nobelia Susanti; Ivan Sunata (Institut Agama Islam Negeri Kerinci, 2024)
The research was carried out because of ineffective planing as evidenced by problems that occurred among employees, namely the lack of effective planing in organizing and directing da'wah activities at KUA Danau Kerinci District. The lack of supervision and monitoring is proven by the problems that occur with employees, namely the lack of supervision and monitoring of employee performance at KUA Danau Kerinci District. The purpose of this research is to determine the application of the Da'wah Management function in improving the performance of employees at the Religious Affairs Office (Kua) of Danau Kerinci District. This study used qualitative research methods. The key informants in this research are the Head of KUA, employees and the public who understand the issues discussed in this research. Data collection techniques use observation, interviews and documentation. Data analysis consists of data reduction, data display and verification and drawing conclusions. The data validity technique uses source (data) triangulation techniques and method triangulation to test the validity of data related to the research problem studied by the researcher. The results of the research are the application of the planing function in improving the performance of KUA employees in Danau Kerinci District, Kerinci Regency in Takhthtih (da'wah planing) including long-term plans and short-term plans. The application of the organizing function in improving the performance of KUA employees in Danau Kerinci District, Kerinci Regency in Tanzhim (organizing da'wah) includes work specialization and departmentalization. The application of the actuating function in improving the performance of KUA employees in Danau Kerinci District, Kerinci Regency in Tawjih (implementation of da'wah) includes providing guidance, providing motivation and establishing communication